Polymorphisms of Immunity Genes and Susceptibility to Otitis Media in Children - Nokso-Koivisto, Johanna; Chonmaitree, Tasnee; Jennings, Kristofer; Matalon, Reuben; Block, Stan; Patel, Janak A. (PloS one, 2014)
Acute otitis media (OM) is a common disease which often develops through complex interactions between the host, the pathogen and environmental factors. We studied single nucleotide polymorphisms (SNPs) of genes involved in innate and adaptive immunity, and other host and environmental factors for their role in OM. Using Sequenom Massarray platform, 21 SNPs were studied in 653 children from prospective (n = 202) and retrospective (n = 451) cohorts. Data were analyzed for the relationship between SNPs and upper respiratory infection (URI) frequency, risk of acute OM during URI episodes, and proneness to recurrent OM. Increased risk for OM proneness was associated with CX3CR1 (Thr280Met) SNP and with a jointly interactive group of IL-10 (-1082) SNP, IL-1β (-511) wild type genotype and white race. Family history of OM proneness independently increased the risk for frequent URIs, OM occurrence during URI, and OM proneness. Additionally, IL-1β (-31) SNP was associated with increased risk for frequent URIs, but IL-10 (-592), IL-1β (-511), IL-5 (-746) and IL-8 (-251) SNPs were associated with decreased risk of URI. IL-1β (-31), CX3CR1 (Thr280Met), IL-10 (-1082) and IL-1β (-511) SNPs were associated with increased risk for frequent URIs or OM proneness.